1994
DOI: 10.1044/jshr.3701.216
|View full text |Cite
|
Sign up to set email alerts
|

Oral Communication Skills of Children Who Are Hard of Hearing

Abstract: Forty children with mild to severe hearing losses were administered a battery of speech and language tasks. The children’s speech was characterized by misarticulation of affricates and fricatives, mild-moderate hoarseness, mild resonance problems, and good intelligibility. Their language samples included syntactic errors, primarily involving the use of bound morphemes and complex sentence structures. The children’s pragmatic errors consisted primarily of providing inadequate or ambiguous information to the lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 20 publications
5
84
0
3
Order By: Relevance
“…[12][13][14][15][16][17] Findings of suboptimal academic skills have been reported in school age children with mild bilateral HL. [27][28][29][30][31][32][33][34][35] Other investigators have reported delayed development of vocabulary and speech skills in children with unilateral HL. 36,37 Although it has been reported that children with unilateral rightsided HL have poorer performance on verbal tests than children with left ear unilateral HL, 16 our cohort was too small and diverse to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Findings of suboptimal academic skills have been reported in school age children with mild bilateral HL. [27][28][29][30][31][32][33][34][35] Other investigators have reported delayed development of vocabulary and speech skills in children with unilateral HL. 36,37 Although it has been reported that children with unilateral rightsided HL have poorer performance on verbal tests than children with left ear unilateral HL, 16 our cohort was too small and diverse to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Elfenbein et al 49 examined the oral language skills of school-aged children with varying degrees of hearing loss. Children with mild hearing loss and those with normal hearing had similar semantic and syntactic skills.…”
Section: Speech Language and Auditory Characteristics Of Children Wmentioning
confidence: 99%
“…1,2 Advocates of early intervention emphasize the importance of maximizing sensitive periods of development to prevent the communication, language, and literacy delays frequently observed in children with mild to moderate/severe losses [3][4][5][6][7] and those with severe to profound losses. 8 -13 Early detection and intervention are believed to be critical steps toward proactive management of these children.…”
mentioning
confidence: 99%